Cropping System-Based Irrigation for Improving Crop and Water Productivity in the Coastal Zone of Bangladesh - SARKER, K K; KAMAR, S S A; HOSSAIN, A; MAINUDDIN, M; BELL, R W; BARRETT-LENNARD, E G; GAYDON, D S; GLOVER, M; SAHA, R R; ALI, M A; KHAN, M S I; MANIRUZZAMAN, M (Journal of the Indian Society of Coastal Agricultural Research, 2019)
The cropping intensity in the coastal zone of Bangladesh is significantly lower than the country’s average. The dominant crop grown in the saline areas is transplanted aman (T. aman) rice. The feasibility of intensified cropping patterns based more efficient water management and the production of two/three crops in a year has not been investigated in the salt-affected areas of Bangladesh. In this study, we tested five cropping patterns to understand their effects on grain yield, water use and water productivity, soil salinity and overall profitability. Field experiments were conducted in farmers’ fields at Amtali, Barguna, Bangladesh, during 2016-2017 and 2017-2018. The cropping patterns were (i) CP1: Mustard - T. aus - T. aman, (ii) CP2: Sunflower - T. aus - T. aman, (iii) CP3: Maize - T. aus - T. aman, (iv) CP4: Wheat - Mungbean - T. aman and (v) CP5: Fallow - Fallow - T. aman. Standard agronomic management practices for each crop were followed. The rice equivalent yield, production efficiency, total system productivity and profitability were all greater in CP2 than other cropping patterns. The marginal benefit-cost ratios were 1.28, 1.60, 1.46, 0.83 and 1.50 for CP1, CP2, CP3, CP4 and CP5, respectively. The soil water contents among the treatments in soil profiles decreased from sowing to harvest but the soil water content was found lower in treatment of CP5 (Fallow - Fallow - T. aman) followed by other cropping patterns. Salt accumulated in soil during the growing season rising from 4 dS m-1 (November) to 9 dS m-1 (March) in 0-60 cm soil profile. The highest soil salinity and osmotic solute potential were recorded in CP5 during February/March. Over the 2 years, the diversified cropping patterns incorporating mustard, sunflower and maize crops (CP1, CP2 and CP3) enhanced the productivity and profitability of the system and represent superior options to one crop per year in the salt-affected areas of Bangladesh.